On the construction of past geographies: Rio de Janeiro, port city 17 century - Abreu, Maurício de Almeida (GEOUSP Espaço e Tempo (Online), 2000)
This article discusses the role of the past in geographical studies. Classical définitions, which have established Geography as a "science of the présent" have severely limited its scope, especially in Brazil. The interprétation of past geographies is as valid a subject for geographers as the study of the présent. Past, présent and future are analytical dim ensions which are shared by ali disciplines; what differentiates them is not the time period they study but the questions they pose to reality. The recent work of Milton Santos on the nature of space provides a good starting point for defending the need for more past geographies. An empirical study of Rio de Janeiro in the 17th century is developed as an example